ANALYSIS OF LANGUAGE STYLE IN THE NOVEL “ORANG ORANG BIASA” BY ANDREA HIRATA AS LITERATURE TEACHING MATERIAL IN SENIOR HIGH SCHOOL - Muzdalifah, Muzdalifah; Efendi, Irfan; Fajri, Khoirul (Transpublika Publisher, 2023)
This study aims to delineate the language styles present in Andrea Hirata's novel